2004
DOI: 10.1108/00070700410516784
|View full text |Cite
|
Sign up to set email alerts
|

The European consumers’ understanding and perceptions of the “organic” food regime

Abstract: This paper explores consumer understanding and perception of organic food, with specific reference to the relatively new concept of organic farmed salmon. Key themes associated with the term “organic” and its meaning, as determined by consumers, are explored and the role of labelling and regulatory authorities considered. Focus groups in five countries (UK, Germany, Spain, Norway and France) consisting of 196 participants showed that most consumers are confused about the meaning of the term organic and are lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(125 citation statements)
references
References 31 publications
7
114
1
Order By: Relevance
“…Eight sessions of Focus Group in the United Kingdom and five in other countries of the European Union were held in order to obtain more knowledge on organic foods and the consumer perception of these foods through a cross-country study. The conclusion drawn was that there is lack of knowledge and confusion among European consumers in relation to the term organic (AARSET et al, 2004). Thus, the motivations towards consumption varied with the country, the culture and the products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight sessions of Focus Group in the United Kingdom and five in other countries of the European Union were held in order to obtain more knowledge on organic foods and the consumer perception of these foods through a cross-country study. The conclusion drawn was that there is lack of knowledge and confusion among European consumers in relation to the term organic (AARSET et al, 2004). Thus, the motivations towards consumption varied with the country, the culture and the products.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the motivations towards consumption varied with the country, the culture and the products. Nevertheless, observing countries such as Germany, England, Australia, the United States, France and Denmark, it is possible to notice that there was a tendency of the organic consumer to privilege firstly the aspects related to health and its connection to foods, secondly the environment, and finally the taste of organic foods (AARSET et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…55% consumers showed less interest in certification, perhaps it could mean as a factor certification is not as important to them or they don't trust organic certification. Canavari et al [8]; Lockie et al, [28]; Aarset et al [1] also found that consumers distrust certifying bodies. 45% consumers who have shown interest in certification are willing to premium between 10-50%.…”
Section: Discussionmentioning
confidence: 99%
“…Consumers are willing to pay a higher price premium for organic logo than for a generic organic label [25], [52]. But some European studies found that consumers tend to distrust certification bodies, leading them to question the genuineness of organic products [8], [28], [1]. Several studies seem to indicate that organic food has been insufficiently promoted and merchandized.…”
Section: H2: Perceived Health Benefits Of Organic Food Positively Infmentioning
confidence: 99%
“…Their focus group outcomes revealed an obvious lack of knowledge among the participants concerning aquaculture in general. It was found that consumers are mostly unfamiliar with aquaculture (Aarset et al 2004). The image of aquaculture seems to be created by comparing it to agricultural systems and by contrasting it with fishing, whilst, at the same time the image of aquaculture being an unsustainable, antibiotic-driven production activity prevailed.…”
Section: Negative Effects Of Aquaculture Production Activities and Comentioning
confidence: 99%